Challenges and Responses: A Tertiary Hospital in 2019-nCoV Epidemic. (14th December 2020) - Li, Hong; Zhang, Zhuo; Li, Ping; Nie, Hu
ABSTRACT: The recent outbreak of coronavirus in Wuhan, China, has imposed challenges on the Chinese medical system. Not only the dramatically increasing number of infected cases and insufficient medical resources, but also the peoples' panic throughout the whole country have made medical services extremely difficult. To respond to these challenges effectively, our hospital implemented an urgent response strategy, including human resources and medical resources preparation and re-allocation, immediate fever screening, strict patient-visiting flow management, and reasonable information communication. Our experience and response measures could provide a reference for other hospitals in the current situation.